Zero-risk weights and capital misallocation - Takuji Fueki; Patrick Hürtgen; Todd B. Walker (Deutsche Bundesbank, 2024)
Financial institutions, especially in Europe, hold a disproportionate amount of domestic sovereign debt. We examine the extent to which this home bias leads to capital misallocation in a real business cycle model with imperfect information and fiscal stress. We assume banks can hold sovereign debt according to a zero-risk weight policy and contrast this scenario to one in which banks weight the sovereign debt according to default probabilities. Banks are assumed to miscalculate the probability of a disaster state due to moral hazard and imperfect monitoring. This distortion pushes the economy away from the first-best allocation. We show that the zero risk weight policy exacerbates these distortions while a non-zero risk-weight improves allocations. The welfare costs associated with zero-risk weight policies are large. Households are willing to give up 3.2 percent of their consumption to move to the first-best allocation, whereas in the economy with non-zero risk-weights households are willing to give up only 1.2 percent of their consumption to move to the first-best allocation.
Keywords: E61; E62; 330; Zero-Risk Weight; Fiscal Limit; Macroprudential Regulation; Sovereign-Bank Nexus; Fiscal Stress